RNase III-Dependent Expression of the rpsO-pnpOperon of Streptomyces coelicolor - Gatewood, Marcha L. (American Society for Microbiology, 2011)

(untitled)
We have examined the expression of the rpsO-pnpoperon in an RNase III (rnc) mutant of Streptomyces coelicolor. Western blotting demonstrated that polynucleotide phosphorylase (PNPase) levels increased in the rncmutant, JSE1880, compared with the parental strain, M145, and this observation was confirmed by polymerization assays. It was observed that rpsO-pnpmRNA levels increased in the rncmutant by 1.6- to 4-fold compared with M145. This increase was observed in exponential, transition, and stationary phases, and the levels of the readthrough transcript, initiated upstream of rpsOin the rpsO-pnpoperon; the pnptranscript, initiated in the rpsO-pnpintergenic region; and the rpsOtranscript all increased. The increased levels of these transcripts in JSE1880 reflected increased chemical half-lives for each of the three. We demonstrated further that overexpression of the rpsO-pnpoperon led to significantly higher levels of PNPase activity in JSE1880 compared to M145, reflecting the likelihood that PNPase expression is autoregulated in an RNase III-dependent manner in S. coelicolor. To explore further the increase in the level of the pnptranscript initiated in the intergenic region in JSE1880, we utilized that transcript as a substrate in assays employing purified S. coelicolorRNase III. These assays revealed the presence of hitherto-undiscovered sites of RNase III cleavage of the pnptranscript. The position of those sites was determined by primer extension, and they were shown to be situated in the loops of a stem-loop structure.